Internalizing Local Wisdom in Tourism Management: A Strategy for Sustainable Tourism in Pangandaran, Indonesia - Ginting, Ayu Rahayu Muliani; Dzakiyyah, Hilwa Dhiyya Haibah; Pratama, Armandha Redo (Politeknik Negeri Bandung, 2025)
This study explores the integration of local wisdom into tourism management as a strategic foundation for sustainable tourism development in Pangandaran, Indonesia. As a coastal tourism destination enriched by the cultural intersection of Sundanese and Javanese communities, Pangandaran presents a unique repository of local values that remain underutilized in current tourism practices. Using a qualitative descriptive approach, data were collected through field observations, literature review, and in-depth interviews with local community members. The findings reveal that the internalization of traditional values—such as the Nampaling festival, Hajat Laut ritual, Sedekah Bumi ceremony, and the cultural norm of Someah ka Semah (hospitality toward guests)—is implemented through community-based planning, coordination, and control mechanisms. These values not only reinforce environmental stewardship and cultural preservation but also enhance social cohesion and local economic benefits. The active participation of local communities ensures the continuity of these traditions while fostering inclusive and sustainable tourism governance. This study concludes that local wisdom, when systematically embedded in tourism management, contributes significantly to sustainable development goals by balancing ecological, socio-cultural, and economic dimensions.